The Effect of Financial Reporting Digitalization and Digital Financial Literacy on MSME Profitability in the Digital Transformation Era - Kurnia Indah Sumunar; Muhammad Hilman Rusydie; Chusnul Maulidina Hidayat (MDP Student Conference, 2026)
Digital transformation becoming more popular in financial management for Micro, Small, and Medium Enterprises (MSMEs), especially in the process of recording and reporting. The financial reporting digitalization enables faster, more accurate, and integrated output, which can enhance decision making in MSMEs. This research examines the effect of digital financial reporting and financial literacy to MSMEs profitability. Using a quantitative survey of 100 MSMEs owners and analyzed with multiple linear regression, this study found that digital financial reporting does not significantly effect on profitability, and financial literacy positively and significantly effect in profitability. This results recommend that adopting digital financial technology can improve business performance and the efficiency of financial reporting. MSME owners and policymakers should apply digital transformation.